2020
DOI: 10.1080/17513758.2020.1733678
|View full text |Cite
|
Sign up to set email alerts
|

A generalized within-host model of dengue infection with a non-constant monocyte production rate

Abstract: In this paper, we generalize a previous model of within-host dengue infection with a nonconstant monocyte production rate. We establish the existence of three equilibria and give some local stability results. We then estimate three parameters in the model from clinical data for dengue virus serotype 2. It is then shown that the model can exhibit behaviours that are not possible under the assumption of constant monocyte production. Lastly, we perform a sensitivity analysis of the model in two contexts, antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Primary DENV dynamics models: During primary infections, the body produces antibodies that neutralize the specifc serotype of the infection (type-specifc responses). Several mathematical models that describe Primary DENV infection within hosts have been studied (see [8][9][10][11][12][13][14][15][16][17][18]). Some related works regarding the immune responses have been investigated in primary DENV infections, including: cytotoxic T lymphocytes (CTLs) responses has been introduced by [8,11,14], a study of both humoral and innate immune responses has been published by [16], humoral immune response [30], Models of both humoral and CTL responses [12,13,17,31].…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary DENV dynamics models: During primary infections, the body produces antibodies that neutralize the specifc serotype of the infection (type-specifc responses). Several mathematical models that describe Primary DENV infection within hosts have been studied (see [8][9][10][11][12][13][14][15][16][17][18]). Some related works regarding the immune responses have been investigated in primary DENV infections, including: cytotoxic T lymphocytes (CTLs) responses has been introduced by [8,11,14], a study of both humoral and innate immune responses has been published by [16], humoral immune response [30], Models of both humoral and CTL responses [12,13,17,31].…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
“…Among the studies that introduced DENV infection, taking into account difusion, was Elaiw and Alof study [25], they modeled a DENV infection with difusion, by taking into consideration the spatial mobility of cells and DENV particles. Furthermore, [25] considered the DENV can infect one target of cells, but there are several works that have indicated that the dengue virus can infect multiple types of cells (e.g., [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]).…”
Section: Primary and Secondary Denv Dynamics Modelsmentioning
confidence: 99%
“…Models pertaining to primary DENV infection within the host have been developed in recent years, with various mathematical formulations available in the literature (refer, for instance, [4] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ). Primary DENV infection models were developed by considering the effect of antibody immunity [2] , [12] , CTL immunity [8] , [9] , [11] , both antibody and CTL immunities [6] , [13] , [14] , [15] , both innate and CTL immunities [10] and both innate and antibody immunities [4] .…”
Section: Introductionmentioning
confidence: 99%
“…During the recent years, several mathematical models have been developed which describe within-host DENV primary infection [9][10][11][12][13][14][15][16][17]. ese models are based on the virus dynamics model introduced by Nowak and Bangham [18].…”
Section: Introductionmentioning
confidence: 99%